An Intercultural Methodology in Area-Based Qur’anic Studies: The Integration of Hermeneutics, Anthropology, and History - Syaifuddin Zuhri (DAAR EL-KAMIL: Multidisciplinary Journal, 2025)
Qur’anic studies in Southeast Asia, particularly in Indonesia and Malaysia, have developed within plural and dynamic socio-cultural contexts, rendering purely textual-normative approaches insufficient to explain the relationship between sacred texts and religious practices in society. This study employs a qualitative library research approach by analyzing primary sources in the form of Qur’anic texts and secondary sources consisting of classical and contemporary literature in the fields of hermeneutics, anthropology of religion, and historical Qur’anic studies. The findings indicate that interreligious and polysemic hermeneutics enable contextual and inclusive readings of the Qur’an, especially in addressing contemporary issues such as gender equality, social justice, and interfaith relations. This approach is reflected in the reinterpretation of normative verses, such as the concept of qawwāmūn (Qur’an 4:34), which is analyzed through the framework of maqāṣid al-sharī‘ah to emphasize substantive justice. Meanwhile, the anthropology of religion plays a crucial role in revealing the disparity between the Qur’an’s normative ideals and the lived religious practices of Muslim communities, without reducing the essence of the text. Instead, it encourages critical reflection and the revitalization of Qur’anic ethical values. The integration of these three disciplines forms an intercultural methodology that not only enriches academic discourse but also carries practical implications for strengthening religious moderation, fostering interfaith dialogue, and promoting inclusive social development in multicultural regions. This study concludes that intercultural methodology constitutes an epistemological necessity in regional Qur’anic studies, as it effectively bridges the universality of revelation with the particularity of local contexts, thereby reaffirming the relevance of the Qur’an as a source of ethical and humanitarian values in modern society.